Genomic Assays in Node Positive Breast Cancer Patients: A Review - Bou Zerdan, Maroun; Ibrahim, Maryam; El Nakib, Clara; Hajjar, Rayan; Assi, Hazem I. (Frontiers in Oncology, 2021)
In recent years developments in breast cancer have allowed yet another realization of individualized medicine in the field of oncology. One of these advances is genomic assays, which are considered elements of standard clinical practice in the management of breast cancer. These assays are widely used today not only to measure recurrence risk in breast cancer patients at an early stage but also to tailor treatment as well and minimize avoidable treatment side effects. At present, genomic tests are applied extensively in node negative disease. In this article, we review the use of these tests in node positive disease, explore their ramifications on neoadjuvant chemotherapy decisions, highlight sufficiently powered recent studies emphasizing their use and review the most recent guidelines.